Tourism Connectivity among Small Islands in the Formulation of a Sustainable Island Tourism Hub Concept in North Gorontalo - Dewi Sartika T. Zees; Muh. Fakhri Jamaluddin; Moh Fadlun Lamusu; Abdul Talib Modaa (Jurnal Penelitian Pendidikan IPA, 2026)
North Gorontalo Regency, characterized by its cluster of small islands, possesses significant potential for the development of marine and cultural tourism. However, limited accessibility, particularly in maritime transport, remains a major constraint. This study employs a qualitative descriptive approach, integrating spatial, environmental, tourism, and supply and demand analyses. Data were obtained through literature reviews, field surveys, and focus group discussions (FGDs) involving stakeholders. The analysis identifies Dudepo Island as having strategic advantages to serve as a sustainable tourism hub, supported by its geographical position, land carrying capacity, existing infrastructure, and potential for sustainable development. The application of the hub-and-spoke model is considered effective in enhancing inter-island connectivity, improving travel efficiency, and supporting the diversification of tourism products. The implementation of the Sustainable Island Tourism Hub concept is expected to strengthen local economic opportunities, promote environmental sustainability, and enhance community welfare.